Emergência e desenvolvimento de fisális produzidas em sombreamento - Mezzalira, Éder Júnior (2016)
The use of shading levels may be an important factor for the development of seedlings of fisális species. Knowing the appropriate levels is essential for the decision making of the nurseryman. Based on the above, the aim with this work was to evaluate the vegetative development of four species of fisális cultivated at different levels in shading. Two experiments were conducted, one in nursery and another in the field. In the first experiment, the treatments were arranged in plots by four levels of shading (25, 50, 75% and cultivation at full sun) and the subplots consisting of four species of Fisális (Physalis peruviana, p. angulata, P. pubescens and P. Minimal). The experimental units were formed of 24 tubes, for a total of 64 units. The experimental design used was random blocks, in subdivided plot diagram 4 x 4, containing four repetitions. In the first 30 days after sowing was evaluated the speed index (IVE) and at 76 days after sowing evaluated the height of plants, stem diameter, number of leaves, foliar biomass and root system and foliar area. For the field experiment plants were used coming from the first experiment, using randomized complete block design in a factorial scheme 4 x 4 (cultivation environments x species), containing four repetitions. The treatments were composed by seedlings formed in a culture environment with 25, 50, 75% shading and full sun and four species of physalis (Physalis peruviana, P. angulata, P. pubescens and P. minima). The experimental units were composed of 4 plants, totaling 64 experimental units. For the field experiment the survival index of the seedlings, number of fruit per plant, fresh fruit and fruit biomass per plant were evaluated, productivity and titratable acidity of the fruits. At the end of the production period the diameter of the stem was evaluated. It can be concluded that the IVE of the four species of fisális increased with 25% of shading. For the initial growth of species of fisalis, the range of 25 to 35% of shading becomes the most indicated. Physalis plants cultivated in the initial phase in an environment with 75% shading presented higher mortality, reaching 52%. Higher plant survival rate in the field transplant, fruit production with larger size and higher productivity occurred with plants maintained at 25% shading.